Misapplication of the Concept of Actual Losses in Pretrial Decision No.113/Pid.Pra/2024/PN.Jkt.Sel - Dana, Robin; Alhadi, Muhammad Nurcholis; Surahman, Surahman; Elviandri, Elviandri (Jurnal Daulat Hukum, 2025)
Corruption is a special crime that is different from general crimes because it requires state financial losses as a basic element. Constitutional Court Decision No. 25/PUU-XIV/2016 emphasizes that corruption must be viewed as a material crime, so that the element of real and definite state losses (actual loss) must be proven investigatively. This concept requires an accurate and final calculation of state losses as part of at least two valid pieces of evidence as specified in Article 184 of the Criminal Procedure Code. This study aims to examine the judge's error in the Pretrial Decision No. 113/Pid.Pra/2024/PN Jkt.Sel, which does not make actual loss a valid piece of evidence in the application of coercive measures against corruption suspects. Using normative research methods through a legal approach and case studies, as well as qualitative analysis, it was found that pretrial judges still use a formal crime approach and accept evidence that does not meet the actual loss standard. This error has implications for legal uncertainty and has the potential to harm the suspect's rights in the criminal process.